ARID3A and ARID3B induce stem promoting pathways in ovarian cancer cells - Dausinas, Paige (Gene, 2020)
ARID3A and ARID3B are paralogs from the AT-Rich interactive Domain (ARID) family. ARID3A and ARID3B associate to regulate genes in B-cells and cancer. We were the first to demonstrate that ARID3B regulates stem cell genes and promotes the cancer stem cell phenotype. Importantly, different knockout phenotypes in mice and distinct patterns of expression in adult animals suggests that ARID3A and ARID3B may have unique functions. In addition, high levels of ARID3B but not ARID3A induce cell death. Our goal was to express ARID3A, ARID3B, or both genes at a moderate level (as can be observed in cancer) and then identify ARID3 regulated genes. We transduced ovarian cancer cells with ARID3A-GFP, ARID3B-RFP, or both. RNA-sequencing was conducted. ARID3A and ARID3B regulated nearly identical sets of genes. Few genes (<5%) were uniquely regulated by ARID3A or ARID3B. ARID3A/B induced genes involved in cancer and stem cell processes including: Twist, MYCN, MMP2, GLI2, TIMP3, and WNT5B. We found that ARID3A and ARID3B also induced expression of each other, providing evidence of the cooperativity. While ARID3A and ARID3B likely have unique functions in distinct contexts, they are largely capable of regulating the same stem cell genes in cancer cells. This study provides a comprehensive list of genes and pathways regulated by ARID3A and ARID3B in ovarian cancer cells.